Promotion of Nitrogen Fixation of Diverse Heterotrophs by Solid-Phase Humin - Dey, Sujan; Kasai, Takuya; Katayama, Arata (Frontiers in Microbiology, 2022)
Although biological nitrogen fixation (BNF) proceeds under mild conditions compared to the energy-intensive Haber-Bosch process, the slow kinetics of BNF necessitate the promotion of BNF activity in its practical application. BNF promotion using purified nitrogenases as well as using genetically modified microorganisms has been studied, but these enzymes are unstable and expensive, and moreover, designing genetically modified microorganisms is also difficult task. Alternatively, BNF promotion in non-modified (wild-type) microorganisms (enriched consortia) with humin has been shown, which is a humic substance insoluble at any pH and functions as an extracellular electron mediator. However, the taxonomic distribution of diazotrophs promoted by humin, the levels of BNF promotion, and the underlying mechanism in BNF promotion with humin remain unknown. Here, we show that taxonomically diverse heterotrophic diazotrophs, harboring nifH clusters I, II, and III, promoted their BNF by accepting extracellular electrons from humin, based on the characterization of individual responses of isolated diazotrophs to humin. The reduced humin increased the acetylene reduction activity of the diazotrophs by 194 % to 916 % compared to the level achieved by the organic carbon source, causing ATP synthesis in the diazotroph cells without increase in the CO2 production and direct electron donation to the MoFe protein of the nitrogenase in the cells without relying on the biological electron transfer system. These would result in BNF promotion in wild-type diazotroph cells beyond their biochemical capacity. This significant promotion of BNF with humin would serve as a potential basis for sustainable technology for greener nitrogen fixation.